Mission-Oriented Life and the Illusion of Worldly Pursuits: An Analysis on Surah Al-Fath (48:29) and Surah Al-Hadid (57:20) - Muhammad Faizul Haque; Md. Mahabub Alom; Mohamed Ashath; Adam Ahmed Shogar (Maklumat: Journal of Da'wah and Islamic Studies, 2026)
In today’s world it is often observed that contemporary secularism and consumerism invite individuals to pursue material preferences and instant rewards. It is also noticed that people preceding life like feeling purposeless and frustrated, like a field working without planting and meaningful seeds on earth. So, this study investigates the Qur’anic view of purposeful life (holistic guided life) by antagonistic two paradigms: life with a divine objective and life gripped in worldly interferences. The present paper studies of Surah Al-Fath verse 29 and Surah Al-Hadid verse 20, how the Qur’an frames believers as divine mission motivated individuals aligned with divine objectives on this earth. And at the same time, it is cautioning against a materialistic, aimless lifestyle rooted in fantasy on the earth. In addition, the present paper emphasizes on highlighting the traits, outcomes, and spiritual paths associated with each model, offering reflections on how these understandings remain relevant to the contemporary Muslims desire a meaningful existence. The current study adopts qualitative methodology based on textual and thematic analysis of selected Qur’anic verses to explore the contrasting concepts of purposeful and materially focused life. Finally, the study concludes that divine guided (qur’anic) life, grounded in tawḥīd, justice, mercy, and moral responsibility on the earth. The divine mission-oriented life also warns the individual that worldly survival is a test only. Thus, human beings are guided to align their activities with divine revelation, avoiding the delusion of temporal attractions. They also advised working in their worldly life in accordance with revelation (Qur’an and Sunnah) in the fields of personal and societal conversion.